2011
DOI: 10.2478/v10032-011-0013-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vermicompost, Fertilizer and Mulch on Plant Growth, Nodulation and Pod Yield of French Bean (Phaseolus vulgaris L.)

Abstract: SummaryIntegration of vermicompost and organic mulch as elements of vegetable production system sustain soil fertility and crop productivity. A field experiment was conducted with the objective to investigate the effects of vermicompost, NPK fertilizer and organic mulch on crop growth, nodulation and pod yield of French bean (Phaseolus vulgaris L.) with an ultimate aim of optimizing water and nutrient requirement in mild-tropical climate during dry season. The shoot growth traits, namely shoot length, number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
21
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 18 publications
8
21
2
Order By: Relevance
“…This might be due to slow and steady supply and availability of nutrients through biocompost and FYM with accelerated mineralization under raised bed condition coupled with increased solubility at 1.0 IW/CPE ratio moisture regime. These results are in accordance with the findings of Singh et al (2011).…”
Section: Growth Characterssupporting
confidence: 93%
“…This might be due to slow and steady supply and availability of nutrients through biocompost and FYM with accelerated mineralization under raised bed condition coupled with increased solubility at 1.0 IW/CPE ratio moisture regime. These results are in accordance with the findings of Singh et al (2011).…”
Section: Growth Characterssupporting
confidence: 93%
“…It was observed that the 100 seed weight was highest in T8 with 75%RDF +25%FYM+lime application. Ramana et al, (2011), Singh et al, (2011 and Haque et al, (2015) also reported this type of information and trend in their earlier research work.…”
Section: Resultsmentioning
confidence: 51%
“…Application of compost to newly reclaimed lands has a positive effect on green bean growth and production (Abdel-Mawgoud, 2006). Vermicompost has a significant positive influence on plant growth, flowering, fruiting, root development, yield and quality of beans (Fernandez-Luqueno et al,2010 andSingh et al, 2011). This study aims to evaluate replacing the mineral fertilizers for producing green beans partly or totally using compost and vermicompost.…”
Section: Introductionmentioning
confidence: 99%